2000
DOI: 10.1002/(sici)1099-0984(200001/02)14:1<21::aid-per367>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of temperament in infancy: stability and convergence of measures

Abstract: This study analyzed the stability of individual differences in temperament and the convergence between two kinds of measures used to assess temperament: maternal report (IBQ and TBAQ), and laboratory measures. Sixty children were assessed at 3, 6, 9 and 12 months of age and their mothers' reports were collected at the same time. Mothers' perceptions of their children's temperament showed high stability across the range of children's ages. In laboratory, however, moderate stability was found only for the period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(31 citation statements)
references
References 45 publications
3
28
0
Order By: Relevance
“…All of these researchers examined the emotional aspects of temperament in various ways. Some examined emotional expressions (states) over time (Carranza Carnicero et al, 2000;Goldsmith & Campos, 1990;Riese, 1987;Rothbart et al, 2000;Sullivan et al, 1992;Wachs et al, 2004), whereas others examined trait emotion (Casalin et al, 2012;Durbin et al, 2007;Neppl et al, 2010;Van den Akker et al, 2010). Durbin et al examined the emotional aspects of temperament using laboratory measures (The Laboratory Temperament Assessment Battery [Lab-TAB]; Goldsmith, Reilly, Lemery, Longley, & Prescott, 1993).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…All of these researchers examined the emotional aspects of temperament in various ways. Some examined emotional expressions (states) over time (Carranza Carnicero et al, 2000;Goldsmith & Campos, 1990;Riese, 1987;Rothbart et al, 2000;Sullivan et al, 1992;Wachs et al, 2004), whereas others examined trait emotion (Casalin et al, 2012;Durbin et al, 2007;Neppl et al, 2010;Van den Akker et al, 2010). Durbin et al examined the emotional aspects of temperament using laboratory measures (The Laboratory Temperament Assessment Battery [Lab-TAB]; Goldsmith, Reilly, Lemery, Longley, & Prescott, 1993).…”
supporting
confidence: 92%
“…Some researchers have focused on infants (Carranza Carnicero, Perez-Lopez, Del Carmen González Salinas, & Martinez-Fuentes, 2000;Goldsmith & Campos, 1990;Riese, 1987;Rothbart, Derryberry, & Hershey, 2000;Sullivan, Lewis, & Alessandri, 1992;Wachs, Pollitt, Cueto, & Jacoby, 2004). Two studies have been conducted in which researchers have examined the stability of the emotional aspects of temperament in childhood (Durbin, Hayden, Klein, & Olino, 2007;Van den Akker, Deković, Prinzie, & Asscher, 2010).…”
mentioning
confidence: 99%
“…In order to compare the present data to another German sample (Vonderlin et al, 2012) a factor analysis was carried out on the IBQ-R scales for each age point. Following Carranza and colleagues (Carranza Carnicero et al, 2000), both stability in parental ratings of infant temperament as well as developmental change were assessed. Stability of the IBQ-R scales was reviewed via Pearson product-moment correlations and developmental changes were reviewed via paired t-tests or Wilcoxon-tests if data were not normally distributed.…”
Section: Strategy Of Data Analysismentioning
confidence: 70%
“…No change was observed in the ratings for Sadness and Duration of Orienting. Carranza Carnicero et al (2000) reported similar developmental changes in the first year of life in a study employing the five subscales of the original IBQ (Rothbart, 1981). Between 3 and 12 months, they observed an increase in Activity Level, Distress to Limitations, Fear and Smiling and Laughter and no changes in Duration of Orienting.…”
Section: Temperament: Longitudinal Analysesmentioning
confidence: 99%
See 1 more Smart Citation